STUDI KOMPARASI ANTARA MODEL PEMBELAJARAN STAD DAN NHT TERHADAP HASIL BELAJAR MATEMATIKA - Purbosari, Witrinicia Sukasiti Dewi; Rasidi, Rasidi (Universitas Muhammadiyah Magelang, 2015)
The purpose of this research was to determine the difference between the model STAD and NHT towards learning outcomes math at 5th grade elementary school Kemirirejo 3 Magelang. The research design is a comparative study with the comparative group pretest-posttest design. This research compares two variables. Research subjects in grade 5 elementary school students Kemirirejo 3 amounted to 74 students. Data analysis is a t-Test. In addition to data obtained from the test, data are also obtained from the documentation. The result of SPSS 22 t = 2,202 and ttable = 1,666. Means Ha acceptable the average value posstest VA affter applying the learning model STAD better value posttest VB after applying the learning model NHT. The result showed that the model STAD more effectively to improve learning outcomes 5th grade math Kemirirejo 3 Magelang of the learning model NHT.